CLOUD TECHNOLOGY DISTANCE LEARNING IN HIGHER MATHEMATICS LEARNING PROCESS - N. Rashevska (Kherson State University, 2013)
The article singles out four types of learning models: the model of distance education without the use of global networks, network model of e-learning, mobile learning model and the model of cloud technologies for distance learning can help you organize the teaching of Mathematics. Mentioned advantages and disadvantages of cloud technologies for distance learning.